Keberadaan Mikroplastik dalam Garam: Kajian Literatur pada Beberapa Kasus di Indonesia - Rahmah Arfiyah Ula; Fita Fitriatul Wahidah; Lilik Erviani; Merinda Nur Indahsari; Sitti Nur Ilmiah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Plastic waste is widely found in the environment. Degraded plastic waste eventually forms microplastics. Microplastic pollution has been widely found in various elements in the environment, such as in water, in the air, in organisms, and in salt. The study of microplastics in salt in Indonesia is still very limited, so a literature review was carried out on research carried out in the time period from 2020 to 2024. The parameters observed included abundance, shape, size, color and type of microplastics. The abundance obtained was between 46 particles/kg to 29 particles/g or assumed to be equivalent to 29,000 particles/kg in coarse salt. The abundance of microplastics in commercial salt was between 40 particles/kg to 306.67 particles/kg. The forms of microplastics found included fibers, films, fragments, filaments, and pellets. The microplastics found were black, transparent, red, blue, green, purple, brown, and white. Meanwhile, the size of the microplastics found was between 0.017 mm to 4.936 mm. Microplastic types were only found in one article, including polyvinyl chloride (PVC), polyurethane (PU), polyester, nylon, and polyethylene terephthalate glycol (PETG).